The interpretative model of the text "Left" by D. Ozersky - Варлыгина, Мария Юрьевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
In the present article the problem of interpretative modeling of an artistic text is considered. The work has a cross-disciplinary status, being guided by the ideas of functionalism, psycholinguistics and receptive aesthetics. The research objective is the modeling of one of the possible interpretations of the song "Left" and the definition of the linguistic means and stereotypic/communicative situations that influence the formation of private and individual meanings of a song. The art system is considered to be a secondary modeling system. The image of the text and the idea of its contents are constructs. Therefore, the process of the creation of meaning lasts for the entire time that one operates with the text, starting from the desire to read it and finishing with reminiscences of the text. As a result of the research, we highlighted two key linguistic factors. The first is the lack of unambiguous connotations on the lexical level, and the second is the active use of artistic tropes that aid in the creation of additional semantic connections.